Deciphering the molecular mechanism of water boiling at heterogeneous interfaces - Konstantinos Karalis (Nature Portfolio, 2021)
Abstract Water boiling control evolution of natural geothermal systems is widely exploited in industrial processes due to the unique non-linear thermophysical behavior. Even though the properties of water both in the liquid and gas state have been extensively studied experimentally and by numerical simulations, there is still a fundamental knowledge gap in understanding the mechanism of the heterogeneous nucleate boiling controlling evaporation and condensation. In this study, the molecular mechanism of bubble nucleation at the hydrophilic and hydrophobic solid–water interface was determined by performing unbiased molecular dynamics simulations using the transition path sampling scheme. Analyzing the liquid to vapor transition path, the initiation of small void cavities (vapor bubbles nuclei) and their subsequent merging mechanism, leading to successively growing vacuum domains (vapor phase), has been elucidated. The molecular mechanism and the boiling nucleation sites’ location are strongly dependent on the solid surface hydrophobicity and hydrophilicity. Then simulations reveal the impact of the surface functionality on the adsorbed thin water molecules film structuring and the location of high probability nucleation sites. Our findings provide molecular-scale insights into the computational aided design of new novel materials for more efficient heat removal and rationalizing the damage mechanisms.